2004
DOI: 10.1002/gene.20029
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific distribution of donor mitochondrial DNA in cloned mice produced by somatic cell nuclear transfer

Abstract: Highly diverse results have been reported for mitochondrial DNA (mtDNA) hetero-plasmy in nuclear-transferred farm animals. In this study, we cloned genetically defined mice and investigated donor mtDNA inheritance following somatic cell cloning. Polymerase chain reaction (PCR) analysis with primers that were specific for either the recipient oocytes or donor cells revealed that the donor mtDNA coexisted with the recipient mtDNA in the brain, liver, kidney, and tail tissues of 96% (24/25) of the adult clones. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…The phenomenon of mtDNA heteroplasmy in the sexual hybrid embryo (D. rerio $ · G. rarus #) was also reported in mammal somatic cell cloned embryos (Steinborn 2002;Han et al 2003;Inoue et al 2004). When exploring the development of cloned embryos derived from transgenic common carp (Cyprinus carpio) nuclei and goldfish (Carassius auratus) enucleated eggs, we also found that the mtDNA of donor and receptor co-existed in the cloned embryos before blood-circulation (Sun et al 2005).…”
Section: Disscussionsupporting
confidence: 70%
“…The phenomenon of mtDNA heteroplasmy in the sexual hybrid embryo (D. rerio $ · G. rarus #) was also reported in mammal somatic cell cloned embryos (Steinborn 2002;Han et al 2003;Inoue et al 2004). When exploring the development of cloned embryos derived from transgenic common carp (Cyprinus carpio) nuclei and goldfish (Carassius auratus) enucleated eggs, we also found that the mtDNA of donor and receptor co-existed in the cloned embryos before blood-circulation (Sun et al 2005).…”
Section: Disscussionsupporting
confidence: 70%
“…In somatic cell NT (SCNT)-derived mice, greater levels of D-mtDNA transmission were detected in offspring derived using adult fibroblasts compared to offspring derived using either immature Sertoli cells or cumulus cells as nuclear donors (Inoue et al 2004). These investigators proposed that the variance in levels of transmission arose from the technique utilized to introduce the donor cell rather than the D-mtDNA copy number introduced into the R-oocyte, as the mitochondrial copy numbers were similar for the various donor cells (Inoue et al 2004).…”
mentioning
confidence: 99%
“…These investigators proposed that the variance in levels of transmission arose from the technique utilized to introduce the donor cell rather than the D-mtDNA copy number introduced into the R-oocyte, as the mitochondrial copy numbers were similar for the various donor cells (Inoue et al 2004). However, if the D-mtDNA outcome were related to the ratio of D-mtDNA to R-mtDNA prior to oocyte reconstruction, then somatic cells having greater mtDNA copy numbers should facilitate the level of DmtDNA persisting in embryos and subsequent transmission to the offspring.…”
mentioning
confidence: 99%
“…Cloning of mammals is achieved by the fusion of an enucleated ovum with a somatic cell. This procedure introduces a small amount of somatic cell mitochondria to the zygote and has been successfully applied to mice (47) and cattle (112). The introduced mtDNA can be detected in various tissues in mice and remains stable during embryonic development.…”
Section: Animal Models Of Mtdna Biologymentioning
confidence: 99%
“…The introduced mtDNA can be detected in various tissues in mice and remains stable during embryonic development. However, during adult life there is evidence of nonneutral segregation of introduced mtDNA, which achieves the highest concentrations in the liver, up to 14% (average 1.7%) (47).…”
Section: Animal Models Of Mtdna Biologymentioning
confidence: 99%